(untitled) (Impetus, 2021)
This article presents the final results of the research “Understanding life experiences of older adults for recognition as a biopsychosocial being from Physical Education” developed at the San Rafael Geriatric Home in Chinauta in the municipality of Fusagasugá, Cundinamarca. The results of the study made it possible to recognize the elderly as a biopsychosocial being which can generate contributions to their community, who live, feel, express themselves and in which their experience is composed of several elements built over the years. The research findings indicate that the life experience of the older adult is significant and that each moment lived allows him to be given the value as a human being and as an adult in a given context and community. To understand the life experiences of the elderly and their recognition as a biopsychosocial being from physical education, the research was based on a hermeneutical historical paradigm with a qualitative approach (Martínez, 2007), (Eisner, 1998); three instruments of information collection, life history, field diary and discussion group were implemented, each in a specific phase of the research.